Le Nouveau Monde selon Du Bartras et Lescarbot : pour une étude des circuits d’imprimés “seconds” - Phillip John Usher (Centre de Recherches sur les Mondes Américains, 2013)
This article studies how the materiality of books participates in the convergence of a literary genre (the epic) and a new subject matter (America). The point is to understand how the spreading of knowledge about America, in non-literary forms, was able to give rise to a second form of knowledge spreading in a literary form. In a first instance, the author takes interest in the Seconde Semaine (1584) by Du Bartas, to study the reltionship that it entertains with the library of travel writing and with cartography; in a second moment, the author takes up the rapport between two texts written by Marc Lescarbot: his mini-epic, La Défaite des Sauvages Armouchiquois (1607) and his Histoire de la Nouvelle France (1609). From these readings, it becomes clear that the possibility that an epic text might evoke the realities of America and thus spread knowledge about this recently discovered continent is intimately tied up with the possibility, on the author’s behalf, of building a library of books as well as with certain practices of reading and writing.